Respuesta :

Answer:

See solutions below

Step-by-step explanation:

a) Given the expressions

x³y and x⁴y³

Find their factors

x³y = (x * x * x * y)

x⁴y³ = (x * x * x * y) * x * y * y

GCF = x*x*x*y

GCF = x³y

The expressions in parenthesis is the GCF. Hence the GCF of x³y and x⁴y³ is x³y

b) For 48m⁶n⁵p⁴ and 20m⁴n⁵p⁶

48m⁶n⁵p⁴ =12 * (4 * m⁴ * n⁵ * p⁴) * m²  

20m⁴n⁵p⁶ = 5 * (4 * m⁴ * n⁵ * p⁴) * p²  

GCF is the expression common to both terms

GCF = 4 * m⁴ * n⁵ * p⁴

GCF = 4m⁴n⁵p⁴

ACCESS MORE